Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5267/j.msl.2016.6.003
|View full text |Cite
|
Sign up to set email alerts
|

The impact of human resource practices on psychological empowerment

Abstract: The main objective of this study is to explain the relationship between human resource management (HRM) and psychological empowerment among the employees who worked for the National Iranian oil company (NIOC). The study population includes all NIOC's 950 employees, where 276 people were randomly chosen as sample study. The survey uses a questionnaire originally developed by Spreitzer (1995) [Spreitzer, G. M. (1995). Psychological empowerment in the workplace: Dimensions, measurement, and validation. Academy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…Hence, hypotheses H1b (CDàPE) and H2b (RRàPE) were supported, whilst hypothesis H3b (TDàPE) was not supported. Similar findings were confirmed by earlier researches also (Arefin et al, 2019;Matsuo, 2019;Moradi & Dashti, 2016). Also, the result confirmed that PE changed a greater level of EE (β = 0.70 and p < 0.001).…”
Section: Discussion and Practical Implicationssupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, hypotheses H1b (CDàPE) and H2b (RRàPE) were supported, whilst hypothesis H3b (TDàPE) was not supported. Similar findings were confirmed by earlier researches also (Arefin et al, 2019;Matsuo, 2019;Moradi & Dashti, 2016). Also, the result confirmed that PE changed a greater level of EE (β = 0.70 and p < 0.001).…”
Section: Discussion and Practical Implicationssupporting
confidence: 91%
“…Several studies found TMP as the key player to increase PE. Although there are different controversial results, many researchers empirically found that TMP (CD, RR, TD) positively and significantly influence PE (Arefin et al, 2019;Matsuo, 2019;Moradi & Dashti, 2016). In the direction of mediating effect of PE, the relationship between TMP and employee outcome has been documented in various research works, but contradictory outcomes have been found in the context of relationship amongst these variables.…”
Section: Linking Talent Management Practices Psychological Empowermen...mentioning
confidence: 99%